Central Administration Specialized in States of the European Union - Ieremie, Maria-Cristiana (Acta Universitatis Danubius. Juridica, 2022)
The way of administrative organization in a state is one of the elements that give it identity. The national peculiarities considerably influence this aspect together with the long historical evolution of each state. It is interesting to analyze the legislative discrepancy in terms of regulations on central public administration institutions in different states of the European Union in order to ascertain the historical and customary imprint on the laws in force.